If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 2(k + 3) + -10 Reorder the terms: 2 = 2(3 + k) + -10 2 = (3 * 2 + k * 2) + -10 2 = (6 + 2k) + -10 Reorder the terms: 2 = 6 + -10 + 2k Combine like terms: 6 + -10 = -4 2 = -4 + 2k Solving 2 = -4 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 2 + -2k = -4 + 2k + -2k Combine like terms: 2k + -2k = 0 2 + -2k = -4 + 0 2 + -2k = -4 Add '-2' to each side of the equation. 2 + -2 + -2k = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -2k = -4 + -2 -2k = -4 + -2 Combine like terms: -4 + -2 = -6 -2k = -6 Divide each side by '-2'. k = 3 Simplifying k = 3
| x^2+2kx+k^2-3k+6=0 | | 2.25(4x-4)=-2t+10x+12 | | 3+k/3=3 | | 2(s+2)=6 | | 3.5=130+10x | | (-4)(p+8)=12 | | 150m-100m+39000=40000-150m | | 22+2z=37+6*z | | 12w-19w-1=13 | | w(w-13)=0 | | -x+2(4-x)=-4 | | Sin(x)=-1 | | 6y=-120 | | 6x=32 | | 16=p-(-3) | | 10m+8b-12=0 | | -15+7x=-79 | | (x+3)+(y-5)=36 | | -25(d+2)= | | 14x+9y=310 | | 16.4(2x+11)=6x+33 | | 2990=4*660+6y | | 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x | | Y-2=-1(x+7) | | 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y |